1984
DOI: 10.1071/ea9840165
|View full text |Cite
|
Sign up to set email alerts
|

Intake, digestion, and nitrogen and sulfur retention in Angora goats and Merino sheep fed herbage diets

Abstract: The voluntary intake and digestion of three pasture hays of varying quality by Angora goats was compared with that by Merino sheep. The excretion and retention of nitrogen and sulfur were also measured. When a high quality hay was given, there were no differences between goats and sheep in the intake of organic matter (68 vs 61 g/kg0.75.d) or in organic matter digestibility (digestible organic matter intake) (72 vs 7 1 %). However, the goats appeared to utilize nitrogen less efficiently than the sheep as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
1

Year Published

1990
1990
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 8 publications
3
12
1
Order By: Relevance
“…Nú ñ ez-Herná ndez et al (1991) reported a higher N digestibility in goats than in lambs when fed mountain mahogany (Cercocarpus montanus) leaves treated or untreated with PEG. Several nutritional studies comparing sheep and goats reported no differences in nutrient digestibility when moderate-or good-quality forages were fed (Isac et al, 1994;Molina Alcaide et al, 2000) but fibre digestibility of low-quality forages was greater in goats than in sheep (Doyle et al, 1984). In our work only ADF digestibility of AHCO and AHCOP diets differed between goats and wethers, being higher for goats, while values for AH diet remained similar for both animal species.…”
Section: Nutrient Apparent Digestibilitycontrasting
confidence: 29%
See 2 more Smart Citations
“…Nú ñ ez-Herná ndez et al (1991) reported a higher N digestibility in goats than in lambs when fed mountain mahogany (Cercocarpus montanus) leaves treated or untreated with PEG. Several nutritional studies comparing sheep and goats reported no differences in nutrient digestibility when moderate-or good-quality forages were fed (Isac et al, 1994;Molina Alcaide et al, 2000) but fibre digestibility of low-quality forages was greater in goats than in sheep (Doyle et al, 1984). In our work only ADF digestibility of AHCO and AHCOP diets differed between goats and wethers, being higher for goats, while values for AH diet remained similar for both animal species.…”
Section: Nutrient Apparent Digestibilitycontrasting
confidence: 29%
“…Bohra (1980) found that goats had lower N losses than sheep when fed the same diet. Doyle et al (1984) reported similar N losses when goats and sheep were fed subterranean clover hay or grass clover hay. However, with a ryegrass diet, goats lost less N than sheep did.…”
Section: N Lossesmentioning
confidence: 73%
See 1 more Smart Citation
“…However, Wilson (1977) suggested that digestibility of high quality forages is similar between goats and sheep but goats are better at digesting low quality forage. In fact, a higher digestible capacity has been found in goats in comparison with sheep when consuming forages with low nitrogen and high lignin contents (Gihad et al, 1980;Doyle et al, 1984;Howe & Barry, 1988;Molina-Alcaide et al, 1997). These differences have been ascribed to a greater retention time of the digesta in the rumen of goats (Watson & Norton, 1982;Domingue et al, 1991) and to interspecies differences in the rumen environment, such as a higher production of microbial protein in goals (Hadjipanayiotou & Antoniou, 1983) or a higher number of cellulolytic bacteria in goats than in the sheep (Gihad et al, 1980).…”
Section: Discussionmentioning
confidence: 92%
“…A large number of plant species are palatable to goats, and they have an ability to browse and graze in inaccessible areas (Henzell 1993;Parkes et al 1996). Goats also survive under adverse environmental conditions due to their ability to survive on low-nutrient fibrous vegetation (Wilson and Mulham 1980;Doyle et al 1984). These characteristics make goats a potential threat to vegetation and the environment.…”
Section: Discussionmentioning
confidence: 99%